Repeated-sprint training in hypoxia induced by voluntary hypoventilation improves running repeated-sprint ability in rugby players - Fornasier-Santos, C.; Millet, G. P.; Woorons, X. (European Journal of Sport Science, 2018)
Purpose: The goal of this study was to determine the effects of repeated-sprint training in hypoxia induced by voluntary hypoventilation at low lung volume (VHL) on running repeated-sprint ability (RSA) in team-sport players.